Heavy metal accumulations in Adelie penguin, Pygoscelis adeliae, and their variations with the reproductive processes - Honda, Katsuhisa; Yamamoto, Yoshiyuki; Hidaka, Hideo; Tatsukawa, Ryo (1986)
P(論文) This paper reports the concentrations and distribution of heavy metals in the organs and tissues of the Adelie penguin collected around Syowa Station, Antarctica, in 1981,and also discusses the changes of heavy metal accumulation with the reproductive activity. The metal concentrations of the whole Adelie penguin were in the order of Fe>Zn>Cu>Mn・Cd>Hg>Pb・Ni. High bioaccumulations of Cd and Hg were observed. Generally, higher concentrations of the metals were found in the liver and kidney. However, the concentrations of Pb, Ni, Hg and Cu were relatively high in feather, and Mn and Zn were higher in the bone. Relatively high concentrations of Mn, Zn and Cd were found in the pancreas. A majority (>60%) of the Fe and Cu burdens in the whole body was in muscle which constituted an average of 50% of the body weight. Relatively high burdens of Mn and Zn were in the bone also, and more than half of the body burden of Cd was found in the kidney. Comparatively high burdens of Cu and Hg were in the feather, especially Hg in the feather was approximately 60% of the body burden. Effect of egg-laying on the body metal contents of adult female was not significant. However, the Fe concentrations in livers of the starved males were higher than those of the females and other males, while the bone Zn showed lower concentrations in males than females. Furthermore, an increase of metal concentrations in the body and a redistribution of body Fe were observed as a result of advanced starvation. departmental bulletin paper